Technology, Entertainment, and Design (TED) Channel as a Tool for Improving Vocational Students' Speaking Skills: Teknologi, Hiburan, dan Desain sebagai Alat untuk Meningkatkan Kemampuan Berbicara Siswa Sekolah Menengah Kejuruan - Anggraini, Nur Ajizah Utami; Santoso, Dian Rahma (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Speaking skills are essential for English language learners, particularly in non-native English-speaking countries like Indonesia. However, many students struggle due to limited resources, unengaging teaching methods, and lack of exposure to authentic spoken English. Specific Background: The TED channel on YouTube offers a potential solution by providing diverse, high-quality spoken English content featuring various accents and speaking styles. Knowledge Gap: While previous studies suggest that TED videos enhance public speaking, limited research explores their effectiveness in improving vocational high school students' general speaking skills. Aims: This study investigates the impact of using TED channel videos on students’ speaking proficiency at SMK Dian Indonesia. Results: A pre-experimental study with pre-test and post-test design was conducted, analyzing data using paired-sample t-tests. Findings revealed a significant improvement in students' speaking skills, with mean scores rising from 71.2 to 79.9 (p < 0.05). Novelty: Unlike prior studies focusing on public speaking, this research highlights TED’s effectiveness in improving general speaking proficiency, particularly in vocational high school settings. Implications: The findings suggest that integrating TED videos into language instruction can enhance engagement and speaking performance, encouraging educators to adopt multimedia tools for language learning. Highlights: TED videos enhance students' pronunciation, fluency, and intonation through exposure to native speakers. Significant score improvement from pre-test to post-test confirms the effectiveness of TED as a learning tool. Multimedia integration in English teaching increases student engagement and motivation. Keywords: TED Channel, Speaking Skills, Vocational Students, Language Learning, Multimedia Teaching